MULTICRITERION TYPOLOGY OF AGRICULTURE: A SPATIAL DEPENDENCE APPROACH - Głębocki, Benicjusz; Kacprzak, Ewa; Kossowski, Tomasz (Quaestiones Geographicae, 2019)
At the turn of the 21st century Polish agriculture intensively changed as the consequence of: 1) the socio-economic transformation that started in 1989, 2) the general transition from a centrally-planned economy to a market economy and 3) Poland’s accession in 2004 to the European Union. In this paper, we try to describe, in a synthetic way, the spatial heterogeneity of development of agriculture in Poland. For this purpose we identified the types of contemporary Polish agriculture. We applied the measures of global (Moran 1950) and local (LISA) spatial autocorrelation devised by L. Anselin (1995) and used their calculations in classification methods. Our dataset consists of 69 variables and 3,069 spatial units at the LAU2 level. As the result of the analysis we identified 20 types of agriculture in Poland and presented their characteristic features. We have paid particular attention to a spatial distribution of identified types. We concluded that the distribution is not only a result of natural or socio-economic conditions and local spatial relationships, but also to a greater extent is still affected by historical conditions (mainly partitions and changes of borders after the First and Second World Wars).